KOMPETENSI KEWIRAUSAHAAN PENGARUHNYA TERHADAP PERKEMBANGAN USAHA KULINER DI KELUARAHAN HARJO SARI 1 - Yayuk Yuliana, Sundari (JURNAL ILMU MANAJEMEN DAN KEWIRAUSAHAAN (JIMK), 2020)
The purpose of this study was to determine the effect of entrepreneurial competence, business development, and product innovation on the development of culinary business. This type of research is explanatory research, with data collection techniques through questionnaires and interviews. The sampling technique uses saturated sample techniques. The sample is 83 culinary businesses. This study uses quantitative analysis techniques. Quantitative analysis uses validity test, reliability test, simple regression analysis, coefficient of determination, significance test (t test). From the t-table test (t count> t table or 8.12> 1.99), so that the entrepreneurial competency variables influence the development of the culinary business. Suggestions that can be given in the study for culinary entrepreneurs in Harjosari I Village, to continue to develop themselves and their business through learning and experience. Not just entrepreneurship, but also important to have entrepreneurial competence. Learn more and take part in entrepreneurial seminars or workshops as an addition to entrepreneurship.